THE EFFECTIVENESS OF HOT SEATING STRATEGY TO IMPROVE THE STUDENTS’ SPEAKING SKILL - Nurul Afifah (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2020)
This research aimed to find out the effectiveness of a hot seating strategy to improve the students' speaking skills at SMP NEGERI 3 Madang Suku III OKU TIMUR. This research adopted a pre-experimental research design. The subject of this research was the first students' of SMP NEGERI 3 Madang Suku III OKU TIMUR which consisted of 31 students with 12 boys and 19 girls. Pre-test and post-test were done to collect the data. The instrument of the test was the oral speaking test. A paired sample t-test was used to compare the data from pre-test and post-test. The finding showed that the Mean score of the pre-test was 46.63 and the mean score of the post-test was 53.27. The value of t-obtained = 2.653 was more than t-table = 2.024 with df = 30 and the value of sig. (2-tailed) was 0.000 less than significance level (? = 0.05).). The conclusion, a hot seating strategy was significantly effective to improve students' speaking skills. It implies that this technique can be used to improve students speaking skills among the many existing methods and techniques.